ANALISIS SEMIOTIKA PADA IKLAN TOKOPEDIA “JADIKAN RAMADHAN KESEMPATAN TERBAIK” DI YOUTUBE - Sagatha, Anka (Journal Communication Specialist, 2022)
This study aims to find out the meaning in the Tokopedia advertisement "Jadikan Ramadhan Kesempatan Terbaik" on Youtube. By doing semiotic analysis using the theory of John Fiske, namely about television codes which are divided into 3 parts, namely the level of reality, the level of representation, and the level of ideology. The data collection technique used in this study is by observing advertisements to obtain data. After that make observations or observations systematically. Observations made by researchers are indirect observations and then perform data analysis techniques with a qualitative descriptive approach. So the meaning that can be concluded from the results of research on the Tokopedia ad "Jadikan Ramadan Kesempatan Terbaik" on Youtube is the love and attention of a mother above all else, anything will be done for the sake of her child so that he can always be happy and never feel troubled.